BUILDING A PROPOSED TRAINING PROGRAM FOR TEACHERS OF E-LEARNING CLASSES ACCORDING TO THE THEORY OF INFORMATION PROCESSING TO DEVELOP VERBAL COMMUNICATION SKILLS - haymaaAbduljawad Hussein Al-Ethari, Dr. Mushriq Mohammad Majwal Al-jubori (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current study aims to develop verbal and verbal communication skills: (speaking and listening), by using a training program based on the theory of information processing to develop the speaking and listening skills of teachers of e-learning classes among children - friendly schools in the province of Najaf. Two lists were prepared that include sub-skills for each of the speaking and listening skills, in addition to preparing a note card to judge the speaking skills of teachers and a listening test prepared by the researcher as well, and building a training program that includes two units, one of which is specialized in training in speaking skills, following the steps prepared by the researcher according to The theory of information processing, and another specialized in training in the skill of listening, and the two research tools were applied to the trainees. Before and after implementing the training program, the results were treated statistically. To find out the extent to which the research objectives have been achieved. The effectiveness of the training program was reached in developing the speaking and listening skills of trained teachers.